Hubungan Lama Menyandang Diabetes Melitus dengan Kualitas Hidup Pasien Klub Prolanis Maleosan Tomohon - Tombokan, Vera D.; Salibana, Hengki E. (Medical Scope Journal, 2025)
Abstract: Data of the 2018 Riset Kesehatan Dasar (Riskesdas) showed that North Sulawesi was ranked 4th in the highest prevalence of diabetes mellitus. In Tomohon City, cases of diabetes mellitus also increase continually from year to year and are one of the five most common metabolic diseases. Prolanis (chronic disease control program) is expected to be a forum to improve health and quality of life of patients with chronic diseases such as diabetes mellitus. This study aimed to determine the relationship between the length of time suffering from diabetes and the quality of life of Prolanis Maleosan Club patients in Tomohon. This was a correlation and analytical study. Samples were 45 prolanis patients of Maleosan club. Data were collected using the WHOQOL-BREF questionnaire and were analyzed using the chi-square test. The results showed that there was no relationship between the length of time suffering from diabetes mellitus and the quality of life of Prolanis patients with a p-value of 0.322. In conclusion, there is no relationship between the length of time suffering from diabetes mellitus and the quality of life among patients of Prolanis Maleosan Club in Tomohon. Keywords: diabetes mellitus; length of suffering; quality of life   Abstrak: Data Riskesdas 2018 menunjukkan bahwa Sulawesi Utara menempati peringkat ke 4 angka prevalensi diabetes melitus tertinggi. Di Kota Tomohon kasus diabetes melitus juga terus mengalami peningkatan dari tahun ke tahun dan merupakan 1 dari 5 penyakit metabolik terbanyak. Prolanis diharapkan dapat menjadi wadah untuk meningkatkan derajat kesehatan dan kualitas hidup pasien penyakit kronis seperti diabetes melitus. Penelitian ini bertujuan untuk mengetahui hubungan antara lama menyandang diabetes dengan kualitas hidup pasien prolanis klub Maleosan Tomohon. Jenis penelitian ialah analitik korelasi dengan sampel 45 pasien. Pengambilan data menggunakan kuesioner WHOQOL- BREF dan data dianalisis menggunakan menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan antara lama menyandang diabetes dengan kualitas hidup pasien dengan nilai p= 0,322. Simpulan penelitian ini ialah tidak terdapat hubungan antara lama menyandang diabetes melitus dengan kualitas hidup pasien prolanis Maleosan Tomohon. Kata kunci: diabetes melitus; lama menyandang; kualitas hidup